(untitled) (Research, Society and Development, 2020)
The communication process is essential for health, however, in certain situations it is flawed, as with persons with hearing impairment. Therefore, the objective of this article was to understand the communication process of the Nursing team in the care of patients with hearing impairment. This is a descriptive study, with a qualitative approach, carried out in a Reference Hospital in the city of Salvador, Bahia, Brazil. The study population consisted of seven nurses and six nursing technicians who worked in the medical clinic sector of the hospital. The collection took place between May and June 2019 through semi-structured interviews. Thirteen interviews were analyzed through the content analysis proposed by Bardin whose result generated three categories: Communication process between nursing professionals and individuals with hearing impairment; Communication strategies developed by nursing in the care of the hearing impaired and Process and qualification in nursing work. Therefore, communication is understood as a basic instrument for health promotion, however, it was found that the use of this practice, for the hearing impaired, by the nursing team is not efficient. In view of this, these professionals seek strategies to minimize the repercussions that put the communication process at risk to these individuals.